Genomic advances in the study of the mosquito vector during avian malaria infection - Irene Hernandez-Caballero; Olof Hellgren; Luz Garcia-Longoria Batanete; L. C. Ranford-Cartwright (Parasitology, 2023)
Invertebrate host–parasite associations are one of the keystones in order to understand vector-borne diseases. The study of these specific interactions provides information not only about how the vector is affected by the parasite at the gene-expression level, but might also reveal mosquito strategies for blocking the transmission of the parasites. A very well-known vector for human malaria is Anopheles gambiae. This mosquito species has been the main focus for genomics studies determining essential key genes and pathways over the course of a malaria infection. However, to-date there is an important knowledge gap concerning other non-mammophilic mosquito species, for example some species from the Culex genera which may transmit avian malaria but also zoonotic pathogens such as West Nile virus. From an evolutionary perspective, these 2 mosquito genera diverged 170 million years ago, hence allowing studies in both species determining evolutionary conserved genes essential during malaria infections, which in turn might help to find key genes for blocking malaria cycle inside the mosquito. Here, we extensively review the current knowledge on key genes and pathways expressed in Anopheles over the course of malaria infections and highlight the importance of conducting genomic investigations for detecting pathways in Culex mosquitoes linked to infection of avian malaria. By pooling this information, we underline the need to increase genomic studies in mosquito–parasite associations, such as the one in Culex–Plasmodium, that can provide a better understanding of the infection dynamics in wildlife and reduce the negative impact on ecosystems.